Combined application of broiler chicken manure and PGPR on growth, yield, and amylopectin content of waxy corn “Kumala F1” - Abdul Latif; Maya Melati; Dhika Prita Hapsari (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2026)
Glutinous corn or waxy corn is often used as a raw material for flour, while sweet glutinous corn is preferred when fresh harvest. Broiler manure is one of the organic fertilizers that can be used in the organic cultivation of sweet glutinous corn, and it needs to be optimized. The addition of plant growth-promoting rhizobacteria (PGPR) can be used to stimulate plant growth and increase fertilization efficiency. The experiment was conducted from March to August 2025 at IPB Experimental Field in Cikarawang B, Dramaga, Bogor. The experiment used s a randomized complete block design with doses of broiler manure and PGPR as treatment factors with 3 replications. The manure doses were 0, 10, 20, and 30 t ha-1, while 2 levels of PGPR were with and without PGPR. The concentration of PGPR was 20 g L-1 and was applied by soaking the seeds for about 30 minutes. The results showed that the average leaf numbers did not differ significantly at 8 weeks after planting. The highest leaf area index was recorded without PGPR application, while PGPR application increased root length. Amylopectin content showed a significant response at the lowest manure dose of 0 t ha-1. Keywords: amylopectin; C:N ratio; nutrient immobilization; sweet waxy corn.